2021
DOI: 10.1038/s41420-021-00583-0
|View full text |Cite
|
Sign up to set email alerts
|

RASSF9 promotes NSCLC cell proliferation by activating the MEK/ERK axis

Abstract: The RAS-associated domain family 9 (RASSF9), a RAS-associated domain family gene, is expressed in a variety of tissues. However, its roles in tumorigenesis, particularly in non-small cell lung cancer (NSCLC), are still not understood well. In the present study, we aimed to examine the potential roles of RASSF9 in NSCLC and the underlying mechanisms. Our data showed that RASSF9 expression was upregulated in NSCLC tissues and cell lines. Increased expression of RASSF9 promotes NSCLC cell proliferation. On the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MAPK-mediated signal transduction is a key factor affecting cell fate processes [ 59 ]. As the core module of the MAPK signal cascade, the MAPK-ERK1/2 signaling pathway is highly conservative [ 60 ]. The extracellular signals are transmitted into the nucleus by ERK1/2 and trigger modifications in the expression of certain proteins in cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK-mediated signal transduction is a key factor affecting cell fate processes [ 59 ]. As the core module of the MAPK signal cascade, the MAPK-ERK1/2 signaling pathway is highly conservative [ 60 ]. The extracellular signals are transmitted into the nucleus by ERK1/2 and trigger modifications in the expression of certain proteins in cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the complex pathogenesis of lung cancer is of great significance for drug development and improvement of the survival rate, which is a promising study area. Aiming at gene alterations, including epidermal growth factor receptor mutation, Kirsten rat sarcoma viral homolog mutation ( 7 , 38 ), epigenetic regulation ( 39 , 40 ) and tumor microenvironment regulation ( 41 ), as well as uncontrolled signaling pathways such as the MEK/ERK signaling pathway ( 42 ) and PI3K/AKT signaling pathway ( 43 ), numerous drugs have been developed and used for the treatment of lung cancer ( 44 , 45 ). In addition, current research has found that certain novel genes are involved in the occurrence and development of lung cancer; for example, MG53 suppressed tumor progression by modulating G3BP2 activity in NSCLC ( 32 ), which is a potential therapeutic target for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Except for KITLG and TMTC3 , the rest of the seven known genes do not appear to be functionally related to chick feather colors ( Table 3 ) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. TSPAN19 was associated with plasma inhibin B levels [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALX1 affected craniofacial development and was also closely related to beak shape in Darwin’s finches [ 48 ]. RASSF9 plays a role in regulating tumor proliferation and maintaining epidermal homeostasis [ 49 , 50 , 51 ]. NTS is a neuropeptide that is involved in the regulation of the central nervous system and digestive system and promotes tumor metastasis, etc.…”
Section: Discussionmentioning
confidence: 99%